A Tunable Dual-Fed Self-Diplexing Patch Antenna - Boukarkar, Abdelheq; Lin, Xian Qi; Jiang, Yuan; Yu, Yi Qiang (IEEE transactions on antennas and propagation, 2017)
We propose a simple and compact design of a tunable self-diplexing patch antenna. Two U-shapes are etched on the same platform to locate the radiating patches which are excited separately using two feed ports. Metalized vias acting like metal walls are applied to reduce the antenna footprint, and to avoid coupling effects when the frequency ratio (fr) approaches 2. The tuning process is achieved by using two varactors properly inserted into the radiating structure. The operating frequencies can be tuned independently with high isolation level. Simulation and measurement results are quite consistent. Measured results show that the lower frequency band ranges from 3.9 to 4.37 GHz with measured peak gain and efficiency of 3.82 dBi-65%, while the upper band ranges from 4.63 to 5.34 GHz with peak gain of 4.48 dBi and peak efficiency of 64%. The self-diplexing antenna achieves an isolation level better than 22 and 32 dB for the lowest fr of 1.05, and the highest fr of 1.37, respectively. The radiation pattern is unidirectional and extremely stable during the frequency tuning of both bands.